Ù†Ù…ÙˆØ°Ø¬ ØªØ¹Ù„ÙŠÙ… Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… Ø¹Ø¨Ø± Ø§Ù„Ø¥Ù†ØªØ±Ù†Øª ÙÙ‰ Ø§Ù„Ø¬Ø§Ù…Ø¹Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© Ø¨Ø¬Ø§ÙˆÙ‰ Ø§Ù„Ø´Ø±Ù‚ÙŠØ© - Rosid, Abdur; Hasanah, Mamluatul; Yurisa, Penny Respati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Learning interaction is an essential element during the online learning process. Therefore, this study offers an internet-based speaking skill learning model. This study aims to describe the process, the problem, and the learning model of learning internet-based speaking skills. This study uses a descriptive qualitative approach with case studies, focusing on learning at state Islamic universities in East Java, Indonesia, The State Islamic University of Maulana Malik Ibrahim Malang, and The State Islamic University of KH. Ahmad Shiddiq Jember. For data collection, the researcher used three methods: first, observation of online speaking learning activities conducted at two universities to find out the steps of learning, secondly interviews were conducted with lecturers who teach speaking courses and also students in the class to find out the obstacles faced. and thirdly documentation in the form of photos of activities and platforms used in the learning process to complete the data. For data analysis, the researcher used the Miles and Huberman method: data collection, data classification, data presentation, and concluding. The findings of the research : (1) that the internet-based speaking skill learning process is based on Personal Learning, (2) There are two problems in learning internet-based speaking skills: Internal Problems that is from the lecturer side cannot explain the whole theme and from the student side; bored and External Problems: electronic constraints related to internet signals and data, (3) internet-based speaking skill learning model That is the interaction between students - students and interactions between lecturers - students. The formal findings of this study are: learning maharah kalam with an internet-based personal learning model based on interaction with synchronous media shows its effectiveness in Islamic universities.